BURPEES TRAINING IS EFFECTIVE ON IMPROVING AEROBIC CAPACITY IN OVERWEIGHT AND OBESE STUDENTS - Ramadina, Verawati; Nurhayati, Ummy A'isyah (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2024)
AbstractStudents with sedentary lifestyles and hectic schedules are prone to fatigue and may see a decline in physical fitness, exacerbated by overweight and obesity. VO2 max reflects an individual's aerobic capacity. This study aims to examine the impact of burpees training compared to MICT on aerobic capacity in overweight and obese students. Method quasi-experimental approach, using pre- and post-test two-group design treatments. The sampling method employed purposive sampling. 22 people participated in the exercise program three times a week for four weeks. The study equipment utilized the Six Minute Walking Test (6MWT) is a measuring instrument for walking as far as possible in six minute with a path length of 15 meters, then calculated using the VO2 maz formula. Result a paired sample t-test, the results indicated that burpee training and MICT had an impact on the aerobic capacity of students who were overweight or obese (P=0.00 P<0.05). The independent sample t-test showed that burpees training and MICT affected the aerobic capacity of students with overweight and obesity conditions (P=0.16 P<0.05). Thus, burpees training has a greater impact on aerobic capacity in overweight and obese students compared to MICT, in future research can carry out further analysis regarding other, more varied exercise to increase aerobic capacity.AbstrakMahasiswa kondisi overweight dan obesitas memiliki tingkat VO2 max yang rendah. Pola hidup mahasiswa yang jarang berolahraga dan memiliki aktivitas yang padat mengakibatkan mudah lelah dan dapat menurunkan kebugaran fisik. Aerobic capacity individu dapat dilihat dari VO2 max. Penelitian ini bertujuan mengetahui perbedaan pengaruh burpees training dan MICT terhadap aerobic capacity pada mahasiswa dengan kondisi overweight dan obesitas. Metode quasi experiment melakukan perlakuan pre dan post test two grub design, menggunakan teknik purposive sampling, sample berjumlah 22 orang dengan program latihan 3x seminggu selama 4 minggu. Instrument penelitian menggunakan Six Minute Walking Test (6MWT) adalah alat ukur berjalan sejauh mungkin selama 6 menit dengan lintasan panjang 15 meter, kemudian dihitung menggunakan rumus VO2 max. Hasil uji paired sample t-test menunjukkan bahwa terdapat pengaruh burpees training dan MICT terhadap aerobic capacity mahasiswa dengan kondisi overweight dan obesitas (P=0,00 P<0,05). Serta uji independent sample t-test menunjukkan bahwa burpees training dan MICT terhadap aerobic capacity mahasiswa dengan kondisi overweight dan obesitas (P=0,16 P<0,05). Dengan demikian, burpees training lebih berpengaruh dari MICT terhadap aerobic capacity pada mahasiswa dengan kondisi overweight dan obesitas, penelitian selanjutnya dapat melakukan analisis lebih lanjut mengenai latihan lain yang lebih bervariasi untuk meningkatkan aerobic capacity.